Coptotermes formosanus and Coptotermes gestroi (Blattodea: Rhinotermitidae) Exhibit Quantitatively Different Tunneling Patterns - Nirmala K. Hapukotuwa; J. Kenneth Grace (Psyche: A Journal of Entomology)
Tunneling behavior and the spatial dispersion of tunnels constructed by the subterranean termites Coptotermes formosanus Shiraki and Coptotermes gestroi (Wasmann) (formerly known as C. vastator Light) (Blattodea: Rhinotermitidae) were examined in foraging arenas. The results indicated that these two termite species construct quantitatively different tunnel systems, supporting visual observations made in earlier studies. Coptotermes gestroi constructed thin, highly branched tunnels, while C. formosanus tended to construct wider and less branched tunnels. Tunnels of C. gestroi showed more spatial dispersion than those of C. formosanus, and this species constructed a larger number of tunnels compared to C. formosanus. The presence or absence of food (wood) within the arena did not influence the tunneling pattern of either species. Although previous observations have suggested that these two termite species exhibit different tunneling behaviors; this is the first quantification of the differences. Comparative studies of the foraging behavior of subterranean termite species contribute to our understanding of their distribution and ecology and may help to improve pest management programs, particularly those based on placement of toxic baits. Moreover, differences in tunneling patterns may reflect different foraging strategies optimized for either tropical (C. gestroi) or subtropical/temperate (C. formosanus) environments.